Genome-wide methylation analysis of early-onset schizophrenia. (30th June 2022) - Srivastava, Anil; Chaudhary, Zanib; Qian, Jessica; Al Chalabi, Nzaar; Burhan, Amer M.; Fischer, Corinne E.; Gerretsen, Philip; Kolla, Nathan J.; Graff, Ariel; Remington, Gary; De Luca, Vincenzo
Abstract : Objective: Schizophrenia (SCZ) is a debilitating disease with a complex genetic cause in which age at onset may reflect genetic vulnerability. Though there has been some association between genetic polymorphisms and age of onset, there has been little exploration of the role of epigenetic processes. We sought to explore the influence of DNA methylation, a key epigenetic mechanism, and its association with the age of onset of illness. Methods: One hundred thirty-eight participants aged 18–75 years and previously diagnosed with SCZ spectrum disorders by the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders (SCID DSM-5) were recruited. Venous blood was collected and genome-wide DNA methylation was quantified using the Illumina Infinium HumanMethylation450 BeadChip array. Individual CpG sites and regions of differential methylation were explored by the age of onset; covariates included age, sex, as well as white blood cell composition. Results: Binary grouping (early vs. late onset) revealed four intergenic CpG sites on chromosome 2 that were above the expected P-value threshold, with hypermethylation of the CpG site cg10392614 most strongly associated with early-onset SCZ. The four most strongly associated CpG sites, including cg 10392614, were intergenic. Continuous analysis revealed the top CpG site to be cg11723066, which is linked to the JAM3 gene, with hypomethylation associated with earlier onset; however, results were below the expected P-value threshold. Conclusion: Studies on DNA methylation in the first-episode psychosis population may help further our understanding of the role of epigenetics in the age of onset of SCZ.